Accumulation of antibiotic resistance genes in full-scale drinking water biological activated carbon (BAC) filters during backwash cycles. (15th February 2021) - Wan, Kun; Guo, Lizheng; Ye, Chengsong; Zhu, Jianwen; Zhang, Menglu; Yu, Xin
Highlights: BAC filters harbored ARGs with high richness and high relative abundance. ARGs accumulated in the biofilm of BAC filter during filter ripening. ARGs accumulation is driven by HGT and changes in bacterial community structure. ARGs and MGEs showed significant positive correlation in filter biofilms. Most ARGs persist in BAC filters despite of the backwashing. Abstract: Biological activated carbon (BAC) filtration, a process widely used in drinking water treatment, was recently reported to harbor antibiotic resistance genes (ARGs). This emerging contamination is poorly understood. This study was conducted to investigate the occurrence of ARGs and bacterial community in full-scale BAC filters during the backwash cycle using high-throughput qPCR and high-throughput sequencing. A total of 178 ARGs were detected in all biofilm samples, with relative abundance ranging from 0.1 to 1.37 copies per 16S rRNA and absolute abundance ranging from 4.48 × 10 7 to 3.09 × 10 9 copies/g carbon. Biofilms sampled from different filters shared most detected ARGs and dominant genera including Bryobacter, Pedomicrobium, Reyranella, and Terrimonas, though their bacterial community structure differed significantly. After backwashing, the relative ARGs abundance increased by 1.5- to 3.8-folds and the absolute ARGs abundance increased by 0.90- to 1.12-logs in all biofilm samples during filter ripening, indicating that ARGs accumulated in filters during this period. Redundancy analysis suggested that such ARGs accumulation was mainly driven by horizontal gene transfer in winter, but highly correlated with the increasing relative abundance of genera Bryobacter and Acidibacter in summer. It was observed that 80.6 %-89.3% of the detected ARGs persisted in the filters despite of the backwashing. Given the high richness and relative abundance of ARGs in BAC filter and the ineffectiveness of backwashing in ARG removal, more stringent downstream disinfection strategies are deserved and more research is necessary to assess potential human health risks due to the persistence of ARGs in drinking water. Graphical abstract: Image, graphical abstract